Pelatihan Pembuatan Curriculum Vitae dalam Bahasa Inggris yang Berbasis Application Tracking System - Suningsih, Sri; Ayuni Putri, Lidya; Hendrawaty, Ernie; Komalasari, Agrianti; Sarumpaet, Susi; Waziana, Winia (Jurnal Nusantara Mengabdi, 2024)
Purpose: One of the most important aspects of creating professional human resources in a company is the recruitment process, in which the company selects the right candidates with the skills and qualifications needed by the company. Applicants who come from college graduates must be able to adapt and be competitive to enter the world of work, and must know and understand how to format a CV that can meet company standards. In line with this, this community service activity aims to provide training in making CVs in English based on the Application Tracking System (ATS). Methodology/approach: The method used was to conduct training in making Curriculum Vitae in English based on the Application Tracking System. Results: The results of this Community Service activity showed that participants experienced increased knowledge regarding how to write a good and appropriate CV based on the Applicant Tracking Platform. Thus, with this job application preparation training, participants can be confident and have a greater opportunity to be superior to their competitors during file selection during the job application process. Limitations: This community service activity cannot identify problems or weaknesses in documents or job application files such as CVs. This training activity contributes to the community, especially students, alumni, and graduates in Bandar Lampung, who are in the process of looking for jobs to broaden their insight and improve their soft skills in writing ideal CVs, and are ATS-friendly so that they have more opportunities to get work and compete for targeted jobs. Contribution: By carrying out community service activities at the Faculty of Economics and Business, University of Lampung, in 2023, it can be concluded that this training activity ran well and improved community skills in writing English CVs based on the Application Tracking System, which is different from the CV they used before participating in this training activity.from the CV they used before participating this training activity.